2001
DOI: 10.1080/108107301750254475
|View full text |Cite
|
Sign up to set email alerts
|

Personal Communication Networks and the Effects of an Entertainment-Education Radio Soap Opera in Tanzania

Abstract: The personal networks of listeners and nonlisteners to an entertainment-education radio soap opera in Tanzania are examined to determine the effects of interpersonal discussion of the soap opera's educational themes of family planning and HIV prevention. Listeners are more likely to discuss these two educational issues in their personal communication networks and are also more likely to have other listeners to the radio program in their personal communication networks. Respondents demonstrate a relatively high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Coleman and colleagues (40) examined the diffusion of information about new drugs through the informal social networks of physicians. Since this study, social network analysis has been used to model the diffusion of public health innovations in several areas, including family planning (27,99,129), reproductive health campaigns (47,138), and HIV education and prevention messages (28,99). Several of the studies of diffusion of family planning information found that having a direct or indirect link to the source of information was associated with either having more knowledge of family planning (27,129,138) or increasing the use of contraceptives (27,138).…”
Section: Information Transmission Networkmentioning
confidence: 99%
“…Coleman and colleagues (40) examined the diffusion of information about new drugs through the informal social networks of physicians. Since this study, social network analysis has been used to model the diffusion of public health innovations in several areas, including family planning (27,99,129), reproductive health campaigns (47,138), and HIV education and prevention messages (28,99). Several of the studies of diffusion of family planning information found that having a direct or indirect link to the source of information was associated with either having more knowledge of family planning (27,129,138) or increasing the use of contraceptives (27,138).…”
Section: Information Transmission Networkmentioning
confidence: 99%
“…It has been argued that modifying risk perceptions needs to take cultural and normative aspects surrounding safer sex into account (Donovan & Ross, 2000). As a result, novel interventions using popular media forms such as television or radio soap operas have been used in an attempt to address issues of gender inequality and limited sexual negotiating power (Mohammed et al, 2001;Shapiro et al, 2003) Initiatives such as these have proven very effective in sexual heath promotion, but remain underused (Bhattarai, 2000). Similarly, interventions which make use of celebrity self-disclosure of HIV status and which are based on the idea of engaging audiences with role model stories, have been shown to have substantial impact in influencing people's behaviour (Kalichman & Hunter, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Edutainment approaches that use broadcast media (radio and television) and performing arts (theater or dramatic arts) are found in the United States (Glik et al, 1998;Glik, Nowak, Valente, Sapsis, & Martin, 2002;Sharf, Friemuth, Greenspon, & Plotnick, 1996;Whittier, Kennedy, St. Lawrence, Seeley, & Beck, 2005) and worldwide (Do & Kincaid, 2006;Farr, Witte, Jarato, & Menard, 2005;Mohammed, 2001;ShefnerRogers & Sood, 2004;. The Centers for Disease Control and Prevention have indicated that using edutainment strategies may be effective particularly in delivering important health information to women, namely, those who are Hispanic or African American, that may influence their health-related attitudes and behaviors (Wilson & Beck, 2002).…”
Section: Interactive Multimedia and Entertainment Educationmentioning
confidence: 99%
“…Edutainment interventions designed to affect changes in health behaviors have been shown to be highly effective, especially with low-literacy audiences who may not initially be motivated to process a message (Freimuth & Quinn, 2004;Singhal & Rogers, 1999). One edutainment strategythe soap opera-has been used successfully in television and radio programs (Mohammed, 2001;Rogers et al, 1999;Vaughan, Rogers, Singhal, & Swalehe, 2000). Soap operas are highly popular mass media dramatic serial broadcasts mainly intended to entertain their audiences.…”
Section: Interactive Multimedia and Entertainment Educationmentioning
confidence: 99%